3D printed hierarchical honeycombs with shape integrity under large compressive deformations. (5th January 2018) - Chen, Yanyu; Li, Tiantian; Jia, Zian; Scarpa, Fabrizio; Yao, Chun-Wei; Wang, Lifeng
Abstract: We describe the in-plane compressive performance of a new type of hierarchical cellular structure created by replacing cell walls in regular honeycombs with triangular lattice configurations. The fabrication of this relatively complex material architecture with size features spanning from micrometer to centimeter is facilitated by the availability of commercial 3D printers. We apply to these hierarchical honeycombs a thermal treatment that facilitates the shape preservation and structural integrity of the structures under large compressive loading. The proposed hierarchical honeycombs exhibit a progressive failure mode, along with improved stiffness and energy absorption under uniaxial compression. High energy dissipation and shape integrity at large imposed strains (up to 60%) have also been observed in these hierarchical honeycombs under cyclic loading. Experimental and numerical studies suggest that these anomalous mechanical behaviors are attributed to the introduction of a structural hierarchy, intrinsically controlled by the cell wall slenderness of the triangular lattice and by the shape memory effect induced by the thermal and mechanical compressive treatment. Graphical abstract: Highlights: A new class of hierarchical honeycombs was designed and fabricated using 3D printing technique. The hierarchical honeycomb exhibits a progressive failure mode under uniaxial compression. Compared with regular honeycombs, improved stiffness and energy absorption have been achieved simultaneously. High energy dissipation at large imposed strains (up to 60%) have also been observed under cyclic loading.